(untitled) (Ágora de Heterodoxias, 2015)
Anxiety disorders impact on a high percentage of the world´s population. Many people who suffer these ailments think that their symptoms are normal responses to daily life experiences. They miss the core root of the problem and increase their health risks due to their slowness for seeking help. The first episode usually appears earlier within people who carry genetic trends than in those who do not carry the gens. However, the risk is universal, mainly when the social environment is pathologic. It is possible to control these anxiety disorders when the resources to treat them are used. The earlier the person seeks for professional treatment the better the prognosis of the ailment.